ANALISIS BIAYA KEMOTERAPI PASIEN KANKER PAYUDARA DAN KANKER SERVIKS DI RSUD ULIN BANJARMASIN - Noor Aisyah; Akhmad Syarifuddin; Putri Amami; Mardiana Mardiana (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
Breast cancer and cervical cancer are the most cancers in Indonesia that require public health action and intervention.Cancer financing at Jamkesmas 2012 ranked second as much Rp.144.7M.The aim of the study was to find out the comparison between the real costs and the INA-CBGs package rates for breast cancer chemotherapy patients and cervical cancer JKN participants in RSUD Ulin Banjarmain.Nonexperimental research method with cross-sectional data design was taken retrospectively from JKN claim file in 2018, the study is comparative.Research samples in cancer patients were 306 episodes of care and 127 episodes of care in cervical cancer patients.Data analysis was tested with one-sample t-test to see the comparison of average real costs with INA CBG rates.Based on the results of one-sample t-test, it shows that in all severity levels(I,II,III) there is a significant difference (p<0.05) between real costs and INA-CBGs package rates, except for the severity of I (class1) values p>0.05. The average cost for breast cancer patients to pay for each chemotherapy, the severity I is Rp.4,496,831 and the severity II is Rp.7,797,032.The average cost in patients with cervical cancer chemotherapy, at the severity level I Rp.3,388,248, the severity level II Rp.3,475,007 and the severity level III Rp.3,535,933.